2015
DOI: 10.3945/jn.114.198010
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Serum Selenium Concentrations Are Associated with Lower Depressive Symptoms and Negative Mood among Young Adults

Abstract: In young adults, an optimal range of serum selenium between ∼82 and 85 μg/L was associated with reduced risk of depressive symptomatology. This range approximates the values at which glutathione peroxidase is maximal, suggesting that future research should investigate antioxidant pathways linking selenium to mood. This trial was registered with the Australian New Zealand Clinical Trials Registry as ACTRN12613000773730.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 24 publications
(38 reference statements)
1
35
0
Order By: Relevance
“…This may also explain why there was no difference found between patients who used extra supplementation and those who did not. Selenium deficiency may lead to cardiomyopathy, depressive symptoms or osteoarthropathy [30,31,32,33]. Elevated Phe values already put PKU patients at risk for mood disturbances [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This may also explain why there was no difference found between patients who used extra supplementation and those who did not. Selenium deficiency may lead to cardiomyopathy, depressive symptoms or osteoarthropathy [30,31,32,33]. Elevated Phe values already put PKU patients at risk for mood disturbances [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…We introduced one at a time to the fully adjusted models of tables 2 and 3 variables representing inflammation (via log(C-reactive protein)), cardiovascular disease risk (via Framingham Global CVD Risk Score), reproductive history (via number of live births), and dietary elements associated with depression. The dietary variables consisted of folate, vitamin B12, zinc, vitamin D (Sarris et al, 2016) and selenium (Conner et al, 2015). Because 21 women who self-reported that they were 0 years postmenopause may actually have been perimenopausal by STRAW+10 criteria (Harlow et al, 2012), we conducted the analyses in Tables 2 and 3 again after excluding these women.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, selenium plays an important role in relieving the mental/psychiatric stress. 25 It shows that selenium deprivation can cause depressed mood and hostile behavior. The turnover rate of some neurotransmitters has been affected by selenium deficiency.…”
Section: Physiological Functions Of Seleniummentioning
confidence: 99%